(untitled) (Damascus University Journal of agriculture sciences, 2023)
This research aims to study some factors affecting the economic yield of cumin and black seed crops in the first settlement area in the governorate of Hasaka. The sample size amounted to 383 farmers, who were selected from 58 villages using a stratified random sampling method from the villages of the study area. The research was carried out using the Excel program to determine costs, revenues, net incomes, correlation and regression coefficients to show the impact of social and economic characteristics of the sample farmers on the economic return resulting from the cultivation of cumin and black seed crops for the average of the two seasons (2018-2019), (2019-2020). The results of the analysis showed that the economic yield of the cumin and black seed crops reached about 2606.0 thousand SP/ha and 2478.2 thousand SP/ha, respectively. It was also found that the most important factors that positively affected the economic return were (the age of the farmer, the experience of the farmer, the educational level, the assistance of the extension units), as increasing each of these factors by one unit will lead to an increase in the economic return by a value of (48, 54, 307, 558). thousand SP respectively, in a row with the stability of the rest of the independent factors, while the total costs have negatively affected the economic return, as the lower the costs by one unit, the higher the economic return 11 thousand SP with the stability of the rest of the independent factors.